PENGARUH PAD, DAU, DBH, DAK, PENERIMAAN PEMBIAYAAN DAN PENANAMAN MODAL TETAP BRUTO TERHADAP ALOKASI BELANJA MODAL DAERAH PROVINSI KAWASAN BARAT DAN TIMUR INDONESIA - Slamet Widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
Government policy to prioritize infrastructure development is not only to increase competitiveness, but also to reduce disparities between regions in Indonesia. The success of infrastructure development requires the role of the central government, regional government, and the private sector. The role of the regional government is realized in the form of capital expenditure allocations in the regional budget. The 2014-2019 RPJMN has set a capital expenditure allocation target in the APBD of 30 percen of total regional expenditure. But in its implementation, not all regions have fulfilled this mandate. This study discusses factors that influence the allocation of capital expenditure in the provinces of the western (KBI) and eastern regions of Indonesia (KTI). The data used is accumulated data on Local Budget (APBD) and Regional GDP for the 2010-2017 period in the provinces in the western and eastern regions of Indonesia. The methodology used is data panel regression using fixed effect model. The aim of the study is to formulate a policy of allocating budget transfers to regions that is more effective in narrowing the gap between the western and eastern regions of Indonesia. The results of Fixed Effect Model show that all variables have a positive effect on government capital expenditure allocation at KBI and KTI. General Allocation Fund (DAU) and Gross fixed capital formation (PMTB) have a positive relationship but do not significantly affect capital expenditure allocation in the KTI and KBI regions.